The Significance of the Holy Qur’an on the Legitimate Intentions - Surat Al-Zalzalah as a Model - Abdel, Abdelhak; Ali , Wissam (Islamic Sciences Journal, 2023)
ABSTRACT This surah is one of the Meccan surahs that talked about the power and greatness of Allah, Blessed and Exalted be He, to change the universe at any moment and in any place he willed, so that his creation can see his greatness and ability to change this universe and that he is the mastermind of it. He glorifies Allah Almighty in his heart and watches him with his wounds, and the Muslim knows with certainty that Allah Almighty is the one who revealed the earthquake to the earth, and the effects that follow the earthquake are all an illustration of the dispersal of creation on the Day of Resurrection, and he does not know where his destiny is and awaits his actions that he presented to Allah Almighty and there he wished. If he only did good, this great picture would give us these great meanings and intentions so that the Muslim would be in constant obedience and constant observance of the limits of Allah.